Analisis Konstraktif Fonologi Bahasa Indonesia dengan Bahasa Mee sebagai Pendekatan Alternatif Pembelajaran Bahasa Indonesia Tingkat SD di Kabupaten Nabire dan Paniai - Simin Althur (Balai Bahasa Provinsi Papua, 2019)
This article is aqualitative research using contrastivea nalysis method for contrasting the Indonesian phonological system with that of the Mee language phonology, spoken by the Mee tribe in the regencies of Nabire and Paniai Papua, in order tofind similarities and differences inthetwo phonological systems. Both have the same sub system in (1)vowels/a/, /i/, /u/, /e/, /o/and rising diphtongs/ay/and/aw/. (2) Both have the same consonant subsystem in (a)bilabial/p/, /b/, /m/, /w/; (b) alveolar/t/, /d/,/n/; (c) velar/k/and/g/;and (d)palatal/y/. (3) Both have these identical phonemes/w/ and /y/ in the initial and medial positions.(4) Both have these syllable patterns V and CV. Differences are observed in(1)the vowel/ə/,which is only found in the Indonesian system.(2) The diphthongs/ey/, /ew/, and/ow/ which are only found in the Mee language. (3) these phonemes: labiodental-fricative/f/; alveolar-fricative/s/and/z/; alveolar-vibrating /r/; lateral/l/; palatal/c/and/j/; lamino-palatal fricative/š/or/sy/;palatal-nasal /ň/or/ny/; velar-fricative/x/or/kh/; velarnasal/ŋ/or/ng/; glottal-fricative /h/ which are only found in the Indonesian system. (4) theconsonants in the Indonesian system can be generally distributed initially, medially and finally,except for/c/, /j/,/g/, /z/, /w/, /y/, /ň/which cannot be found finally, and the phoneme/ŋ/cannot be found initially. (5) Oonly the Indonesian system has consonant clusters, and (6) the Indonesian system has the following syllable patterns VC, CVC, CCV, CCVC, CCCV, CCCVC, CCVCC, CVCC while the Mee system only has these patterns V and CV.